2016
DOI: 10.1002/admi.201600431
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Magnetite Mesocrystalline Films: Toward Structural Evolution from 2D to 3D Superlattices

Abstract: This study describes synthesis and detailed characterization of 2D and 3D mesocrystalline films produced by self‐assembly of iron oxide (magnetite) truncated nanocubes. The orientational relations between nanocrystals within the superlattice are examined and atomistic models are introduced. In the 2D case, two distinct superstructures (i.e., translational order) of magnetite nanocubes can be observed with p4mm and c2mm layer symmetries while maintaining the same orientational order (with [100]magnetite perpend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 55 publications
5
98
0
2
Order By: Relevance
“…Effect of added OA on EDPSE assembly. Previous reports have suggested that the addition of amphiphilic molecules such as OA can have an important effect on the assembly process and it has been speculated that the effect can be related to an improved colloidal stability 26,45,46 , reduced evaporation rate 28,43 , and an OA-induced interparticle depletion attraction 37,47 . We have performed a study to clarify how the amount of additional OA influences the EDPSE assembly process.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of added OA on EDPSE assembly. Previous reports have suggested that the addition of amphiphilic molecules such as OA can have an important effect on the assembly process and it has been speculated that the effect can be related to an improved colloidal stability 26,45,46 , reduced evaporation rate 28,43 , and an OA-induced interparticle depletion attraction 37,47 . We have performed a study to clarify how the amount of additional OA influences the EDPSE assembly process.…”
Section: Resultsmentioning
confidence: 99%
“…Note the kinetic stability of mesocrystals and its relation with the transient fusion of constitutive nanocrystals towards single crystals . (i) Mesocrystals formed via particle self‐assembly are exemplified by monolayers of magnetite nanocrystals made of coexisting domains with c2 mm and p4 mm symmetries . (ii) Mesocrystals derived from additive‐controlled phase transformations are illustrated by the hierarchical structures of the sea urchin spine, comprised of space filling, co‐oriented Mg‐calcite nanocrystals embedded in an amorphous matrix .…”
Section: On the Nature Of Materials Precursorsmentioning
confidence: 94%
“…The fourth approach i. e. spatial confinement produces increases in local particle densities, thereby promoting inter‐particle interactions and driving self‐assembly (Figure f). This approach is exemplified by reaction environments based on emulsions, solvent evaporation or Langmuir‐Blodgett films, which are capable of generating complex organization including 2D and 3D architectures ,. Recent work from our group demonstrates the synthesis of 2D and 3D mesocrystalline films via the evaporative self‐assembly of iron oxide truncated nanocubes …”
Section: Pathways To Complex Organizations Of Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle supercrystals have been of great interest for their new emergent properties including plasmonic [1][2][3] , optical [4][5][6] , electrical 7,8 , and magnetic 9,10 properties which cannot be achieved by individual nanoparticles. The emergent properties of nanoparticle supercrystals originate from collective interaction between nanoparticles and are determined by the crystal symmetry 11,12 and lattice parameters 13 as well as composition 14 .…”
Section: Introductionmentioning
confidence: 99%